A Study of State and Society in Ancient India the Views of V.S. Smith: Unraveling the Legacy of John Smith in Ancient India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
John Smith was an English explorer, soldier and writer best known for his role in establishing the first permanent English colony in the New World at Jamestown, Virginia. Smith's legend has grown over the centuries, in particular due to the popular story of his involvement with Pocahontas, a Native American princess. However, Smith was a notorious self-promoter, and the truth of that tale may never be known. Much of what is known about Smith comes from his own writings, which include multiple versions of events and enhance Smith‘s role. George Percy, a fellow Jamestown leader and eventual governor of Virginia, described Smith as ―an Ambityous unworthy and vayneglorious fellowe. Smith‘s self-aggrandizing personality has cast doubt on his claims since the 1600s, and his legacy remains controversial today.